Aberrant RNA splicing is the major pathogenic effect in a knock‐in mouse model of the dominantly inherited c.1430A>G human RPE65 mutation. Issue 4 (25th January 2019) - Li, Yan; Furhang, Rachel; Ray, Amanda; Duncan, Todd; Soucy, Joseph; Mahdi, Rashid; Chaitankar, Vijender; Gieser, Linn; Poliakov, Eugenia; Qian, Haohua; Liu, Pinghu; Dong, Lijin; et al.
Abstract: Human RPE65 mutations cause a spectrum of retinal dystrophies that result in blindness. While RPE65 mutations have been almost invariably recessively inherited, a c.1430A>G (p.(D477G)) mutation has been reported to cause autosomal dominant retinitis pigmentosa (adRP). To study the pathogenesis of this human mutation, we have replicated the mutation in a knock‐in (KI) mouse model using CRISPR/Cas9‐mediated genome editing. Significantly, in contrast to human patients, heterozygous KI mice do not exhibit any phenotypes in visual function tests. When raised in regular vivarium conditions, homozygous KI mice display relatively undisturbed visual functions with minimal retinal structural changes. However, KI/KI mouse retinae are more sensitive to light exposure and exhibit signs of degenerative features when subjected to light stress. We find that instead of merely producing a missense mutant protein, the A>G nucleotide substitution greatly affects appropriate splicing of Rpe65 mRNA by generating an ectopic splice site in comparable context to the canonical one, thereby disrupting RPE65 protein expression. Similar splicing defects were also confirmed for the human RPE65 c.1430G mutant in an in vitro Exontrap assay. Our data demonstrate that a splicing defect is associated with c.1430G pathogenesis, and therefore provide insights in the therapeutic strategy for human patients. Abstract : While RPE65 mutations are almost invariably recessively inherited, RPE65 c.1430A>G (p.D477G) reportedly causes autosomal dominant retinitis pigmentosa. To study this perplexing RPE65 mutation, we generated a knock‐in (KI) mouse model. Rather than being a missense mutation only, c.1430A>G disrupts Rpe65 splicing, greatly affecting RPE65 protein expression. Under regular mouse husbandry, both WT/KI and KI/KI have functionally normal retinal responses. However, following shortened dark adaptation, KI/KI, but not WT/KI, exhibit 40–60% decrease in scotopic ERG response compared to WT. Also, KI/KI are susceptible to light‐induced retinal degeneration.